Association Between Reproductive Health Knowledge, Attitudes, and Premarital Sexual Behavior Among Adolescents: A Cross-Sectional Study in West Java, Indonesia - Masluroh, Masluroh; Rismayanti, Tetin; Lestari, Heni; Latifah, Latifah; Suciati, Suciati; Rahayu, Maria (Journal of Applied Nursing and Health, 2026)
Background: Adolescence is a critical developmental stage associated with increased vulnerability to premarital sexual behavior (PSB). Limited reproductive health (RH) knowledge and negative attitudes are recognized risk factors, yet most Indonesian studies have been conducted in single-school settings. Therefore, this study aimed to examine the association between RH knowledge, attitudes, and PSB among adolescents across three senior high schools in West Java, Indonesia. Methods: A cross-sectional descriptive-correlational study was conducted among 108 adolescents from three senior high schools in West Java in 2025 (total sampling, n=36 per school). Data on reproductive health (RH) knowledge, attitudes, and premarital sexual behaviour (PSB) were collected using validated questionnaires and analysed using Chi-square (χ²) tests in SPSS v.26, with statistical significance set at p<0.05. Results: More than half of respondents demonstrated insufficient RH knowledge (55.5% at SMK Texmaco; 41.7% at SMAN 18; 44.5% at SMAN 2). Negative or insufficient attitudes toward RH were found in 38.9%, 44.5%, and 38.9% of adolescents at the three schools, respectively. High-risk PSB—defined as engagement in intimate contact beyond hand-holding, including hugging, kissing, or more advanced sexual contact, a classification grounded in Indonesian cultural and religious norms where any non-platonic physical contact outside marriage carries significant health and social risk—was prevalent across all sites (44.5%, 47.2%, and 38.9%). Chi-square analysis revealed statistically significant associations between RH knowledge and PSB at all three schools (χ²=8.43, df=2, p=0.015, V=0.28 at SMK Texmaco; χ²=7.21, df=2, p=0.027, V=0.25 at SMAN 18; χ²=6.89, df=2, p=0.032, V=0.24 at SMAN 2 Babelan), and between attitude and PSB at SMK Texmaco (χ²=9.67, df=4, p=0.008, V=0.29). Conclusion: Reproductive health knowledge and attitudes were significantly associated with premarital sexual behaviour (PSB) among adolescents. Strengthening school-based reproductive health education may help promote healthier behaviours, while further longitudinal studies are needed to confirm these findings.